Hadis Tentang Metode Pendidikan Islam - Natia Hasibuan; Siti Ardianti; Bahri Sitompul, Syaiful; Abdul Rahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This writing explains the methods used in Islamic education from a hadith perspective. The purpose of this writing is to know and understand the meaning of Islamic education methods, describe the methods that can be used in Islamic educations. This writing is included in the qualitative type, the writing carries out data mining from several related books and journals using basic studies and analysis that support the written data, from here the writer obtains additional data which is then classified and presented. The results that the author got were Islamic education methods which have also been mentioned by Allah SWT, including: lectures, ajwab questions, targhib, tarhib, stories and parables. Even though each method can facilitate learning, an educator must remain careful in choosing a teaching method.